Identification of a peroxisomal-targeted aldolase involved in chlorophyll biosynthesis and sugar metabolism in rice - Zhang, Fei (Plant science : an international journal of experimental plant biology, 2016)
Copyright © 2016 Elsevier Ireland Ltd. All rights reserved.